Professional Review of the Work Tasks of Nuclear Medicine Physicians: Analysis of Compliance with Normative Requirements and Actual Work Activity - Tatyana S. Klimenko; Mehirban M. Abdullaeva (Peoples' Friendship University of Russia (RUDN University), 2024)
Nuclear medicine is rapidly advancing simultaneously in several areas, which include: developing and producing radiopharmaceuticals (RPs), manufacturing diagnostic equipment and creating related infrastructure, as well as modeling competences for specialists working with a complex category of patients. Due to the novelty and large scale of the tasks associated with the implementation of these advancements, which directly concern nuclear medicine doctors, there is a need to describe their professional profile as a key component of the entire system. The purpose of this work was to conduct a professional analysis of the current work tasks of nuclear medicine doctors to subsequently identify the degree of compliance between the actual activities carried out and existing regulatory requirements. To collect professional material, semi-structured interviews were conducted with doctors of various specialties in the field of nuclear medicine, which were supplemented by an analysis of personnel, information and reference, and administrative documentation of organizations. However, as it turns out, the documentation (professional standards) regulating the activities of nuclear medicine doctors is currently either in the process of development or approval, or simply missing. The documents that currently regulate the activities of doctors do not fully reflect the actual work tasks performed due to the fact that nuclear medicine employees are "interdisciplinary" specialists. The case study of radiologists shows that in order to carry out their work, they need to undergo a system of double certification of activities, and then subsequent training directly on the job under the supervision of an experienced physician mentor. The current situation in nuclear medicine highlights several problem areas related to: (1) determining the degree of adequacy of existing educational programs for the subsequent full implementation of their activities by doctors; (2) discussing the problem of additional burden on employers and, as a result, on employees acting as mentors; and (3) identifying specific additional labor functions and tasks associated with working with high-tech equipment (sophisticated medical devices or medical information systems), which for the most part are not unified and depend on the organization. The developed professiograms for a radiologist and a radiotherapist, taking into account real work tasks, which can be divided into several blocks, can become the basis for creating targeted training programs for specialists, monitor in real time the features of adaptation of specialists to the requirements of nuclear medicine and reasonably resolve issues of selecting doctors to the appropriate medical centers.